Competence Approach in Conditions of Economy Digitalization - E. V. Altukhova (Вестник Российского экономического университета имени Г. В. Плеханова)
The key tool of economy development is new technologies, whose implementation is possible in conditions of new technological structure. Today the trends have been identified, which should be taken into account in plans of the leading companies’ development and final indicator values that should be attained for these plans fulfillment in the future. The program of digital economy development includes as a priority line of modernization the system of education and science, where personnel training requires detail investigation. Now special attention in training specialists is paid to moulding profiles with specific approaches not only in the teaching process organization but in realizing education technologies. The article analyzes views of Russian and overseas researchers on the idea of professional competence. Priority trends of shaping professional competences of the bachelor course graduates were studied, as well as methodological re commendations on their realization. The author provides schemes aimed at introduction to the system of bachelor training certain innovational education technologies meant for mastering a wider range of competences, which can help adapt to the changing conditions of labour market. Approaches were formulated, which could coordinate interests of employers, universities and students with regard to new requirements of economic development.